WarungSync: Development of an Android-Based Integrated Warung Management Application Using Kotlin and Firebase - Muh. Akbar; Ahmad Dinejad Halik (ARRUS Journal of Engineering and Technology, 2026)
This study aims to design and develop WarungSync, an Android-based integrated warung management application intended to assist micro, small, and medium enterprise (MSME) owners in digitalizing their daily business operations. The majority of traditional warung businesses in Indonesia are still managed manually, resulting in inaccurate stock data, unrecorded transactions, and the absence of systematic financial reporting. This study employs the Waterfall software development methodology, consisting of five sequential phases: requirements analysis, system design, implementation, testing, and deployment. The application was built using the Kotlin programming language with Model-View-ViewModel (MVVM) architecture and Firebase as the cloud backend infrastructure, encompassing Firebase Authentication for user security and Firebase Firestore for real-time data synchronization. The results demonstrate that WarungSync successfully integrates Point of Sale (POS) and inventory management functions within a single mobile platform, featuring a real-time dashboard, smart inventory management with low-stock notifications, a digital cashier system, sales reporting with weekly chart visualization, and automated cloud synchronization. The findings of this study reveal that all 13 functional features of WarungSync passed Black Box Testing, confirming that the application operates in accordance with the specified functional requirements and is capable of replacing conventional manual management practices in warung businesses.